Association Between Fasting and Anxiety: A Systematic Review and Meta-Analysis - Mahmood Moosazadeh; Zahra Foroughi; Moloud Fakhri; Samaneh Farnia; Seyed Hassan Nikookar; Motahareh Kheradmand (Journal of Mazandaran University of Medical Sciences)
Background and Purpose: Depression and anxiety disorders are increasing globally and represent major public health concerns. The relationship between fasting and the physical, social, psychological, and mental health of both healthy individuals and those suffering from various diseases has been reported in several studies. This systematic review aims to determine the association between fasting and anxiety. Materials and Methods: This systematic review examined studies, including cohort, case-control, cross-sectional, and clinical trials, that explored the relationship between different types of fasting and anxiety. In this study, the population (P) consisted of participants with fasting experience, the intervention (I) was fasting, the comparison (C) was between the periods before and after fasting, and the outcome (O) was the level of anxiety before and after fasting. International databases, including Google Scholar, Medline, Scopus, Web of Science, and ScienceDirect (up to the end of 2021), were searched using the keywords "anxiety" and "fasting" in both English and Persian. The extracted data were entered into a checklist, which included the researcher's name, type of study, year of implementation, instrument used, type of fasting, and the mean and standard deviation of anxiety scores before and after fasting. Data were analyzed using Stata software (version 11). To estimate the difference in standardized means, the number of samples, the mean, and the standard deviation of the anxiety scores were extracted from the primary studies. Using the Metan command, the random-effects model, and Cohen's estimator, the standardized mean difference in anxiety scores with a 95% confidence interval was calculated. Heterogeneity between the results of the primary studies was assessed using the Q statistic and I-squared index, and publication bias was evaluated using the Begg and Egger tests. The NOS checklist was used to evaluate the quality of the included studies. Results: A total of 1,408 articles were retrieved, of which 13 were related to the topic. Four articles were excluded from the analysis because they did not report the mean. Finally, nine articles were included in the systematic review (nine studies) and meta-analysis (eight studies). The results of the eight studies included in the meta-analysis using the random-effects model showed that the standardized mean difference of the anxiety scores before and after fasting, with a 95% confidence interval (-1.14, -0.21), was estimated to be -0.67. Additionally, the results of the meta-analysis, stratified by the type of fasting and the questionnaire used in the primary studies, indicated that the overall estimate of the standardized mean difference in anxiety scores before and after fasting was not significant when considering the data collection tool and the type of fasting. Based on the heterogeneity indices (I-squared: 93.9%, Q= 114.88, P<0.001), the level of heterogeneity between the results of the primary studies was high. Publication bias was evaluated using the Begg (P=0.322) and Egger (P=0.753) tests, which indicated that publication bias was not significant. Conclusion: The results of this systematic review and meta-analysis showed that the average anxiety score after fasting decreased by 0.67 units (67%) compared to before fasting, indicating a significant reduction in anxiety following a period of fasting.